Ursolic Acid Protects Neurons in Temporal Lobe Epilepsy and Cognitive Impairment by Repressing Inflammation and Oxidation - Liu, Kun-mei; Huang, Yue; Wan, Pan-pan; Lu, Yun-hua; Zhou, Ning; Li, Juan-juan; Yu, Chun-yang; Chou, Jin-jiang; Zhang, Lianxiang; Zhang, Chun; Qiang, Yuan-yuan; Zhang, Rui; et al. (Frontiers in Pharmacology, 2022)
Temporal lobe epilepsy (TLE) is characterized as an impaired ability of learning and memory with periodic and unpredictable seizures. Status epilepticus (SE) is one of the main causes of TLE. Neuroinflammation and oxidative stress are directly involved in epileptogenesis and neurodegeneration, which promotes chronic epilepsy and cognitive deficit. Previous studies have shown that ursolic acid (UA) represses inflammation and oxidative stress, which contributes to neuroprotection. Here we demonstrated that UA treatment alleviated seizure behavior and cognitive impairment induced by epilepsy. Moreover, UA treatment rescued hippocampal neuronal damage, aberrant neurogenesis, and ectopic migration, which are commonly accompanied by epilepsy occurrence. The present study demonstrated that UA treatment remarkably suppressed the SE-induced neuroinflammation, evidenced by activated microglial cells and decreased inflammation factors including TNF-α and IL-1β. Likewise, the expressions of oxidative stress damage markers and oxidative phosphorylation (OXPHOS) enzyme complexes of mitochondria were also remarkably raised following the UA treatment, suggesting that UA suppressed the damage caused by high oxidative stress and the defect mitochondrial function induced by SE. Furthermore, UA treatment attenuated GABAergic interneuron loss. Therefore, our study clarified the notable anti-seizure and neuroprotective properties of UA in pilocarpine-induced epileptic rats. The effect of UA mainly relied on its anti-inflammatory and anti-oxidant ability. Our results indicate a potential advantage of UA application in ameliorating epileptic sequelae.